Community-Based Empowerment in Kaki Langit Market Tourist Village Bantul Yogyakarta - Yunita, Wiwin; Suryono, Yoyon (KnE Social Sciences, 2019)
This research study was conducted to observe activity designs of community-based empowerment in order to find the result of the empowerment through tourist village development. The method employed in this study was descriptive qualitative. The instruments used to collect the data were observation, intervews, and documentation. The applied data analysis techniques were data collection, data reduction, data display, and conclusion drawing. The result of this study pointed that the applied designs of the community-based empowerment were: association, mentoring, funding, construction of facilities and infrastructure, cooperation, and formation of organizations. The implemented model or design hit its target. The target was determined based on the community needs. The results of the implementation of the empowering program were independence and economic improvement of the community. Keywords: Community Empowerment, Tourist Village, Community